Work-related risk factors for sciatica leading to hospitalization - Euro, Ulla (Sci Rep, 2019)
The aim of this study was to assess the effects of the general strenuousness of work and various physical exposures on the risk of hospitalization for sciatica. The study population consisted of Finns aged 30 to 59 who had participated in a national health examination survey in 1978–80 (N = 3891). The participants were followed up until the end of 2011 and information on work-related determinants was acquired by a questionnaire. After adjustment for confounders, sedentary work involving handling fairly heavy objects/physically light work (HR 1.57; 95% CI 1.05–2.34), lifting or carrying heavy objects (2.10; 1.35–3.26) and exposure to whole-body vibration (1.61; 0.95–2.72) predicted sciatica, whereas heavier workloads appeared to reduce its risk (0.48; 0.26–0.89). There was an interaction between body mass index and exposure to whole-body vibration for the risk of sciatica. Overweight (1.94; 0.96–3.93) and obese (3.50; 1.44–8.46) participants exposed to whole-body vibration were at an increased risk of sciatica. Individuals of normal weight who were exposed to vibration, and overweight and obese individuals who were not exposed to vibration were not at an increased risk. The risk of hospitalization for sciatica seems to be highest among obese individuals exposed to whole-body vibration and among those lifting or carrying heavy objects.